Electronic structure of the S1 state in methylcobalamin: Insight from CASSCF/MC-XQDPT2, EOM-CCSD, and TD-DFT calculations - Kornobis, Karina; Kumar, Neeraj; Lodowski, Piotr; Jaworska, Maria; Piecuch, Piotr; Lutz, Jesse J.; Wong, Bryan M.; Kozlowski, Pawel M. (Journal of computational chemistry, 2013)
The methylcobalamin cofactor (MeCbl), which is one of the biologically active forms of vitamin B12, has been the subject of many spectroscopic and theoretical investigations. Traditionally, the lowest‐energy part of the photoabsorption spectrum of MeCbl (the so‐called α/β band) has been interpreted as an S0→S1 electronic transition dominated by π→π* excitations associated with the CC stretching of the corrin ring. However, a more quantitative band‐shape analysis of the α/β spectral region, along with circular dichroism (CD), magnetic CD, and resonance Raman data, has revealed the presence of a second electronic transition that involves the CoCMe bond weakening. Conversely, the lowest‐energy excitations based on transient absorption spectroscopy measurements have been interpreted as metal‐to‐ligand charge transfer (MLCT) transitions. To resolve the existing controversy about the interpretation of the S1 state of MeCbl, calculations have been performed using two independent ab initio wavefunction‐based methods. These include the modified variant of the second‐order multiconfigurational quasi‐degenerate perturbation theory (MC‐XQDPT2), using complete active space self‐consistent field orbitals, and the equation‐of‐motion coupled‐cluster singles and doubles (EOM‐CCSD) approach using restricted Hartree–Fock orbitals. It is shown that both ab initio methods provide a consistent description of the S1 state as having an MLCT character. In addition, the performance of different types of functionals, including hybrid (B3LYP, MPW1PW91, TPSSh), generalized‐gradient‐approximation‐type (GGA‐type) (BP86, BLYP, MPWPW91), meta‐GGA (TPSS), and range‐separated (CAM‐B3LYP, LC‐BLYP) approaches, has been examined and the results of the corresponding time‐dependent density functional theory calculations have been benchmarked against the MC‐XQDPT2 and EOM‐CCSD data. The hybrid functionals support the interpretation in which the S1 state represents a π→π* transition localized on corrin, while pure GGA, meta‐GGA, and LC‐BLYP functionals produce results consistent with the MLCT assignment. © 2013 Wiley Periodicals, Inc. The existing controversy regarding the π → π* versus metal‐to‐ligand charge transfer (MLCT) interpretation of the lowestenergy part of the photoabsorbtion spectrum (α/β band) of methylcobalamin (MeCbl) is explored theoretically. Time‐dependent density functional theory calculations are benchmarked against two ab initio wavefunction‐based methodologies: the second‐order multireference perturbation theory and the equation‐of‐motion coupled‐cluster singles and doubles approach. The advantage of generalizedgradient‐ approximation‐type over hybrid functionals is demonstrated, indicating the MLCT nature of the S0 → S1 transition.